2011
DOI: 10.1074/jbc.m111.266890
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Excess Succinate and Retrograde Control of Metabolite Accumulation in Yeast Tricarboxylic Cycle Mutants

Abstract: Cellular and mitochondrial metabolite levels were measured in yeast TCA cycle mutants (sdh2⌬ or fum1⌬) lacking succinate dehydrogenase or fumarase activities. Cellular levels of succinate relative to parental strain levels were found to be elevated ϳ8-fold in the sdh2⌬ mutant and ϳ4-fold in the fum1⌬ mutant, and there was a preferential increase in mitochondrial levels in these mutant strains. The sdh2⌬ and fum1⌬ strains also exhibited 3-4-fold increases in expression of Cit2, the cytosolic form of citrate syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(47 citation statements)
references
References 46 publications
1
43
0
2
Order By: Relevance
“…The TCA cycle is compromised in cells experiencing mitochondrial defects, but flux through the pathway can be maintained by the action of the RTG pathway (Liu and Butow, 1999; Lin et al, 2011), which is a major function of the RTG pathway (Butow and Avadhani, 2004). Glutamate can suppress the requirement for the retrograde pathway in the TCA cycle by increasing metabolic flux (Liu and Butow, 1999).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The TCA cycle is compromised in cells experiencing mitochondrial defects, but flux through the pathway can be maintained by the action of the RTG pathway (Liu and Butow, 1999; Lin et al, 2011), which is a major function of the RTG pathway (Butow and Avadhani, 2004). Glutamate can suppress the requirement for the retrograde pathway in the TCA cycle by increasing metabolic flux (Liu and Butow, 1999).…”
Section: Resultsmentioning
confidence: 99%
“…How does the RTG pathway control ethanol-dependent filamentous growth without involving other major filamentation regulatory pathways? One possibility is that the RTG pathway is part of the sensing/signaling mechanism that controls the rate of flux through the TCA cycle (Liu and Butow, 1999; Lin et al, 2011). TCA cycle rate is dependent on carbon and nitrogen levels, which are key inducers of filamentous growth in yeast and other fungal species.…”
Section: Discussionmentioning
confidence: 99%
“…This effect would be mediated by a succinate efflux for SDHx mutated cells. Analyses of compartmentalized levels of TCA cycle metabolites have revealed that yeast with sdh Δ mutations may aberrantly efflux succinate from the mitochondria to the cytosol [54]. Other studies have even reported that succinate could be excreted into the medium during cultivation of yeast sdh Δ mutants [55, 56].…”
Section: B Emerging Stromal Cell-succinate-18f-fdg Imaging Phenotypementioning
confidence: 99%
“…Вместе с тем при гипоксии дыхательная цепь митохондрий не может принять на себя водород от какого-либо иного субстрата, кроме янтарной кис-лоты, так как только при ее окислении водород по-ступает на наиболее близкий к кислороду участок дыхательной цепи, что является удобным и эко-номным в энергетическом плане для организма [8]. Феномен активного окисления сукцината получил название эффекта монополизации дыхательной цепи [9].…”
Section: Original Researchesunclassified